The Prognostic Value of the EASIX Score in Patients with Metastatic Pancreatic Cancer - Vahit Can Cavdar; Yalcin Gokmen; Mert Aric; Tugba Altunkaya; Cennet Gizem Erdem; Ilkay Gulturk; Cigdem Usul Afsar (Diagnostics)
Background/Objectives: Pancreatic cancer (PC) is an aggressive malignancy with a poor prognosis, frequently diagnosed at a metastatic stage. The identification of accessible, cost-effective prognostic biomarkers is critical for optimizing treatment strategies. The Endothelial Activation and Stress Index (EASIX), calculated using lactate dehydrogenase (LDH), creatinine, and platelet count, reflects endothelial dysfunction and has shown prognostic value in hematological cancers. However, its utility in metastatic PC remains unexplored. This study is the first to evaluate the prognostic significance of the EASIX in patients with metastatic PC receiving first-line FOLFIRINOX chemotherapy. Methods: This retrospective cohort study analyzed 204 patients diagnosed with metastatic pancreatic adenocarcinoma at Istanbul Training and Research Hospital between 2020 and 2025. All patients received FOLFIRINOX as first-line therapy. EASIX was calculated as LDH (U/L) × creatinine (mg/dL)/platelet count (109/L). A cut-off value of 1.33 was used to stratify patients into low and high EASIX groups. Overall survival (OS) was assessed using Kaplan–Meier analysis and compared with the log-rank test. Results: The mean patient age was 63.0 ± 9.4 years; 61.8% were male. There were no significant differences in baseline characteristics between groups. Patients with EASIX ≥ 1.33 had significantly lower platelet counts and higher LDH and creatinine levels. Median OS was 14 months for EASIX < 1.33 and 8 months for EASIX ≥ 1.33 (p < 0.001). Conclusions: EASIX is a simple, inexpensive prognostic marker associated with overall survival in metastatic PC. Its integration into clinical practice may facilitate early risk stratification. Further prospective studies are needed to confirm its prognostic utility.